Metrical Alteration in the Poetry of Abid Siraj al-Din - Karwan Ahmed Hamad; Yadgar Rasul Balaki; Sabah Rashed Qadir (Zanco Journal of Human Sciences, 2026)
This research, titled "Metrical Alteration in the Poetry of Abid Siraj al-Din," is an attempt to identify and verify the two types of Metrical Alteration (Metrical Elision): Consonant-compatible Metrical Alteration and Incompatible Metrical Alteration. The purpose of the Metrical Alteration (Metrical Elision) is what is stated in the rules and adhered to by the poet until the end of the poem. While the non-adhering rhyme (Incompatible Metrical Alteration) is the type that the poet does not consistently follow; if it appears in one verse, it is not necessarily used in the following verses. In addition to the introduction, the research is divided into two main sections. The first section is dedicated to theoretical aspects, where the terms of rhyme are analyzed, the concept of Metrical Alteration 'Zihaf' is presented in its simple and compound forms, and then each type is defined. As for the second section, it is dedicated to categorizing types of Metrical Alteration. This section is divided into nine main topics, each dedicated to a particular type of Metrical Alteration. After identifying the Metrical Alteration, they are presented in specific chart.